Analysis of Business Strategy in Improving Product Marketing - Mulyan Pulubuhu; Abdul Rahman Kadir; Muhammad Sobarsyah (Magister Management, Hasanuddin University, 2022)
This study aims to analyze the business strategy in improving the product marketing of PT. JAMKRIDA SulSel, a credit guarantee company, through SWOT Analysis approach and BCG Matrix. Guarantee companies play a major role in supporting economic development in the context of providing guarantees to Banks or Non-Bank Financial Institutions regarding access to financing or credit for the implementation of development projects and assisting small, micro and medium enterprises (MSMEs). The research design is explanatory with a qualitative descriptive approach without any hypothesis testing by analyzing the company's strategic factors. Data were collected through observation, interviews, and documentation studies at PT. JAMKRIDA SulSel. The analytical techniques in this study are IFAS and EFAS analysis, SWOT analysis, and BCG Matrix Analysis. The results showed that the position of the company is in Quadrant I (Progressive). The SWOT analysis also suggests alternative implementations of the S-O Strategy. The BCG Matrix shows that credit guarantee products from rural banks or Bank Perkreditan Rakyat (BPR) are in the “Stars” quadrant; credit guarantees from Bank Sulselbar are in the “Cash Cows” quadrant; and credit guarantees from the Revolving Fund Management Institution or called Lembaga Pengelola Dana Bergulir (LPDB) and Surety Bond products are in the “Question marks” quadrant.